A randomized clinical trial to compare P. falciparum gametocytaemia and infectivity following blood-stage or mosquito bite induced controlled malaria infection - Bousema, Teun; Alkema, Manon; Reuling, Isaie; de Jong, Gerdie; Lanke, Kjerstin; Coffeng, Luc; van Gemert, Geert-Jan; van de Vegte-Bolmer, Marga; de Mast, Quirijn; van Crevel, Reinout; Ockenhouse, Christian; Ivinson, Karen; et al. (Dryad, 2019)
For malaria elimination efforts, it is important to better understand
parasite transmission to mosquitoes and to develop models to allow early
clinical evaluation of transmission-blocking interventions. We previously
described a Controlled Human Malaria Infection protocol for induction of
gametocytemia in malaria naïve volunteers by mosquito bite (CHMI-trans)
(Reuling et al., 2018).  Here, we compared gametocyte production
and infectivity in the CHMI-trans model after bites of Plasmodium
falciparum (Pf)- infected mosquitoes  to that after intravenous
administration of  Pf-infected-erythrocytes.  Volunteers
received (sub) curative treatments with gametocyte-permissive piperaquine
or sulfadoxine-pyrimethamine. Blood-stage inoculation induced considerably
higher gametocyte densities compared to mosquito bitesthat was predicted
by PfAP2-G transcripts indicative of gametocyte commitment, and resulted
in Pf-positive mosquito infections in 9/12 volunteers versus 0/12
volunteers after mosquito bite inoculation. Current findings firmly
establish the CHMI-trans with intravenous administration of asexual
parasites as a model for early clinical evaluation of interventions that
aim to interrupt Pf-transmission.
Keywords: FOS: Biological sciences; Malaria